STUDY OF COASTLINE CHANGES MODELLING IN PRAJAGUMIWANG RIVER DOWNSTREAM AREA, KARANGSONG BEACH, INDRAMAYU - Abdurrahman, Umar
Karangsong Beach, Indramayu, had changed in the beach process characteristics. The beach process was originally dominated by erosion, then dominated by accretion. The change in characteristics was caused by the jetty construction in 2005 – 2007. The construction of the jetty structure was causing changes in the pattern of sediment transport rates and coastline changes. This study aimed to examine changes in sediment transport rates and coastline pattern due to jetty construction on Karangsong Beach. Beach processes analysis can be done by utilizing image data from Google Earth. The errors in determining coastlines caused by manual digitization process and tidal phenomena from Google Earth image data resolved by calculating uncertainty. This study also simulated sediment transport rates and shoreline changes to analyze beach process using the UNIBEST-CL model. The hydrodynamic factors considered were waves and the longshore component of tidal flows. The longshore component of tidal flow had a maximum value of 0.088 ms-1. Meanwhile, the waves at Karangsong Beach were dominated by waves that travel from the north, with a low significant wave height 0.5 – 1 m and the wave period was between 4 - 5 seconds. The variability of wave direction, significant wave height, and wave period had a significant influence on the value of sediment transport rates. After the jetty construction, in the northern and southern regions, the rate of sediment transport at the Karangsong Beach dominated towards the southeast. The largest sediment transport rate and net sediment transport rate occurred between 2008 and 2009 with the value 28.950 m3/yr and 28.865 m3/yr respectively. In the northern region, the sediment transport rate hindered by the presence of jetty, hence that the region experienced accretion. In the southern region, the supply of sediment blocked from the northern region replaced by sediment supply from the Prajagumiwang River and had a significant influence. The pattern of sediment transport rates and coastline change are showing fluctuation values which decreases over time.